Optimization of organization and access to basic spatial data - Rikanovič, Rada; Smole, Domen (Geologija, 2005)
Geologic Survey of Slovenia acquired, in the last few years numerous digital spatial data of various sources and scales. Amounts of data constantly increased which lead to considerations on their organization in a unique collection to which the users could have direct access. For surveying the already organized spatial data the ESRI ArcIMS program was selected, whereas for organization of spatial data themselves and for certain specific users requirements (cropping of raster data to a selected domain) the mentioned GIS internet solution had to be upgraded with additional program modules. In the following paper factual internet GIS Solutions shall be presented especially from the aspect of simplification and increased efficiency of existing working procedures.